PENERAPAN MODEL PEMBELAJARAN BERBASIS KEARIFAN LOKAL BERORIENTASI KARAKTER TERHADAP KEMAMPUAN MENULIS BERBAHASA INGGRIS MAHASISWA DI IPTS - GABBY MAUREEN PRICILIA (Jurnal Education and Development, 2019)
One of the curriculum’s expectations at the fourth semester of english department in Institut Pendidikan Tapanuli Selatan (IPTS) is students are able to write narrative text. But in fact, students’ writing narrative text ability is still low, so researcher conduct a research in that field. The purposes of this research are to find out: 1) the extent of students’ writing narrative text ability, and 2) the significant effect of using character oriented local wisdom based learning model on students’ writing narrative text ability at the fourth semester students of english department in IPTS. The method of research is mix method by combining quantitative and qualitative method. The researcher collected the data by using interview and composition writing test. The sample was taken by using total sampling technique, it was 25 students. The data were then analyzed by using descriptive and inferential analysis, it was t-test formula by Arikunto. The findings of the research are the mean score of students’ writing ability before using character oriented local wisdom based learning model was 53.54 which categorized bad, then after using character oriented local wisdom based learning model was 82.50 which categorized good. The hypothesis testing showed that t-test was higher than t-table, it means that the hypothesis is accepted. It clearly seen that there is a significant effect of character oriented local wisdom based learning model on students’ writing narrative text ability at the fourth semester students of english department in IPTS.